The effects of the Supreme Court ruling by Chief Justice Godfrey Chidyausiku in the case of Nyamande and Anor v Zuva on labour relations: the case of Zimbabwe’s parastatals - Seyani, Alinafe K. M. (Midlands State University, 2017)
Zimbabwe is facing a huge amount of inequity in terms of labour relations due to the Supreme Court ruling of 17 July 2015 by Chief Justice Godfrey Chidyausiku in the case of Nyamande and Anor V Zuva. This instability within parastatals has become a common feature as the ruling triggered mass terminations on notice without benefits. Morale within the work place subsequently hit a low and by the end of September 2015 it had led to over 30 000 job terminations. The rights workers had prior to the ruling were rendered insignificant thus they were stripped. Those that tried to ensure that their rights were being preserved did so with the risk of termination as the order of the day became termination on notice. This was facilitated by the Supreme Court making it clear that the only prerequisite for firing an individual was adequate notice which ranged from three months to two weeks depending on the nature of the employment contract. The main thrust of this research was to find the effects of the ruling on labour relations within parastatals in Zimbabwe The researcher used qualitative research to complete this study as effectively as possible. Purposive sampling was employed and thereafter, document analysis, questionnaires as well as interviews were used in order to collect data from research participants. A content analysis was thereafter used as the data analysis tool in this study. Ethical concerns played a major role as they contributed to the manner in which the research was executed. All the research tools were used in order to amass knowledge on the effects that the ruling had on labour relations within parastatals, which it was able to do. Effects of the ruling which were unpacked within the study were termination on notice, unfair dismissal, no job security, limitations on unionism and collective action and retrenchment without severance packages. The research findings revealed that the ruling had adverse effects and since it was done it formed the basis of meagre and conflict riddled labour relations in the country and countered the efforts of ZIMASSET in job creation. The results made it evident that there was need for the Labour Amendment Act of 2015 to be formulated. The government is recommended to put in place instruments to ensure cordial labour relations within parastatals. The employers are recommended to employ prudence in terms of firing, while employees, to lobby for their rights and an amicable work environment. Research findings have enabled the conclusion that labour relations within Zimbabwe’s parastatals are largely impacted by external stakeholders.